Respuesta :

Answer:

The correct answer is C.

Step-by-step explanation:

In order to solve this problem, you need to simplify the equation by using a natural log (ln). This will cancel out the e and make it easy to solve.

e^(2x + 5) = 4 ----> Take the ln

lne^(2x + 5) = ln(4) ------> Simplify

2x + 5 = ln(4) ------> Subtract 5

2x = ln(4) - 5 -----> Divide by 2

x = [ln(4) - 5]/2

Answer:

Answer: The bottom or last answer.

Step-by-step explanation:

e^(2x + 5) = 4            Take the ln of both sides.

ln(e^(2x + 5)) = ln(4)  Modify the left side. When e^z is logged you get z

2x + 5 = ln(4)             Subtract 5

2x + 5-5 = ln(4) - 5     Simplify

2x = ln(4) - 5               Divide by 2

x = [ ln(4) - 5]/2           Answer

ACCESS MORE